Consumer Perception Towards Ready-To-Eat Food Products: Exploring the Factors Influencing Consumer Decisions in the Ready-To-Eat Food Market (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Due to pressure from their way of life, Indians have started favoring quick and simple methodsof cooking rather than taking their time. Most often, individuals, especially young ones, choose quickfoods like Nestle cup noodles, Bhel, etc. Ready-To-Eat Food Stuffs have recently gained popularity inIndia for a number of reasons, including convenience, flavor and texture, packaging, and marketingtactics. Dal Curries, Instant Poha, Rapid Upma, Instant Idly Dosa Mix, Sandwiches, Ready Masals Curry Powders, Indian Snacks, etc. are a few examples of ready-to-eat food items. The elements thataffect customers' decisions to purchase and consume ready-to-eat food products are covered in thisessay.